Comprehensive Logistics - Gudehus, Timm.; Kotzab, Herbert; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
Modern logistics comprises operative logistics, analytical logistics and management of logistic networks. Central task of operative logistics is the efficient supply of required goods at the right place within the right time. Tasks of analytical logistics are designing optimal networks and systems, developing strategies for planning, scheduling and operation, and organizing efficient order and performance processes. Logistic management plans, implements and operates logistic networks and schedules orders, stocks and resources. This reference-book offers a unique survey of modern logistics. It contains proven strategies, rules and tools for the solution of a multitude of logistic problems. The analytically derived algorithms and formulas can be used for the computer-based planning of logistic systems and for the dynamic scheduling of orders and resources in supply networks. They enable significant improvements of performance, quality and costs. Their application is demonstrated by several examples from industry, trade and service providers. Apart from corrections and modifications the second edition contains a new chapter on maritime logistics. It demonstrates how the methods of this book can be used to solve complex logistic problems of practical relevance for economy, society and environment. The book is written for professionals, scientists, teachers and graduate students. An extensive index makes it a dictionary of modern logistics.
Part I: Principles, Strategies and Organization -- Tasks and Aspects of Modern Logistics -- Organization, Scheduling and Control -- Planning and Realization -- Potential Analysis -- Strategies -- Logistic Costing and Controlling -- Logistic Pricing and Marketing -- Time Management -- Random Processes and Dynamic Forecasting -- Order Scheduling and Production Planning -- Inventory Management -- Logistics Units and Master Data -- Limit Performances and Queuing Effects -- Purchasing, Sales and Logistics -- Part II: Systems, Networks and Operations -- Logistic Networks and Systems -- Storage Systems -- Commissioning Systems -- Transport Systems -- Design of Logistic Halls -- Production Logistics -- Optimal Networks and Supply Chains -- Logistic Service Providers -- Maritime Logistics -- People and Logistics.
Keywords: Engineering; Engineering economy; Business planning; Engineering; Engineering Economics, Organization, Logistics, Marketing; Control, Robotics, Mechatronics; Organization/Planning.